Clinical indications for plain abdominal radiographs: A survey study among radiographers - Lynn Burrell; Razana Williams; Wilma ten Ham-Baloyi (AOSIS, 2023)
Background: Abdominal pain is a common complaint in the Emergency Department. Radiographers' knowledge and practices regarding clinical indications for performing abdominal examinations are crucial in the results radiographs produced. Aim: To determine the knowledge and practices of radiographers regarding the clinical indications for performing radiographic examinations of the abdomen. Setting: Four public hospitals in the Eastern Cape province, South Africa. Methods: A cross-sectional study was conducted, using a convenience, all-inclusive sample of n = 85 radiographers. A hard copy self-administered questionnaire was distributed between February and June 2020. Descriptive (mean and standard deviations) and inferential (chi² test) statistics were generated using IBM® SPSS® version 26.0 software package. Results: Knowledge of clinical indications had a mean of 59.41. All four demographics (age, years of experience, attended a short course and attended pattern recognition course) were significantly associated with overall knowledge. Additionally, short course attendance was significantly associated with most practice items, and two knowledge items (which views are done for perforation; and which view(s) demonstrate a stab abdomen). Pattern recognition was significantly associated with one knowledge item (which views are regarded as an acute abdomen). Conclusion: Despite the lack of short courses and pattern recognition courses, radiographers' knowledge of clinical indications was good (50%). Continuous training, accessible protocols for performing clinical indications for plain abdominal radiographic examinations for radiographers, audit, feedback and reminders to enhance protocol adherence are recommended. Contribution: The study findings could be used to enhance knowledge and practices regarding clinical indications for plain abdominal radiographic examinations among radiographers.